2002
DOI: 10.1055/s-2002-36044
|View full text |Cite
|
Sign up to set email alerts
|

Vorteile von Biomatrices bei der Chondrogenese von pluripotenten mesenchymalen Stammzellen

Abstract: The systematic investigation of biomatrices by chondrogenic progenitor cell culture systems may lead to important data for the evaluation of the chondrogenic potency biomatrices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 58 publications
0
1
0
1
Order By: Relevance
“…We used additional bone marrow aspirates combined with bone grafting in 3 cases to achieve a maximum of cell potential within the area to be regenerated. Different authors reported on the possible use of progenitor cells from different tissues like bone marrow and periosteum with or without scaffolds for bone and cartilage repair [1,2,7,13,17,28,34]. Although there are no clinical trials with a longer follow up, the high potential of these cellbased strategies is evident.…”
Section: Discussionmentioning
confidence: 99%
“…We used additional bone marrow aspirates combined with bone grafting in 3 cases to achieve a maximum of cell potential within the area to be regenerated. Different authors reported on the possible use of progenitor cells from different tissues like bone marrow and periosteum with or without scaffolds for bone and cartilage repair [1,2,7,13,17,28,34]. Although there are no clinical trials with a longer follow up, the high potential of these cellbased strategies is evident.…”
Section: Discussionmentioning
confidence: 99%
“…Das gleiche Problem verhinderte die Anwendung kommerziell erhältlichen Fibrinklebers als Trägermaterial (van Susante et al, 1999). Zum anderen werden MACT-Matrizes durch Fibrinkleber im Defektareal befestigt (Aicher et al, 2003) und Biomaterialien zwecks Verbesserung der Adhäsion mit Fibrin beschichtet (Jager et al, 2002 (Kock et al, 2011 (Li et al, 2005;Chung et al, 2006;Welsch et al, 2010).…”
Section: 523) Gewebeersatzverfahren: Osteochondraler Autograftunclassified